Peningkatan Kemampuan Membaca Permulaan Anak PAUD Imanuel Maubele Melalui Media Kartu Bergambar - Efrems Hendro Loe Loko; Otje Arman Sunbanu; Salmon Amtiran; Rinawati Br. Perangin Angin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Early childhood, commonly referred to as AUD (Anak Usia Dini), is the period from birth to six years old, which is crucial for the development of character and personality. At this stage, support from both parents and teachers is essential to help optimize children's potential according to their characteristics. One important aspect of early childhood development is language skills, which include listening, speaking, writing, and reading. Reading is a fundamental ability, as it serves as the foundation for developing other skills. In kindergarten-aged children, reading ability is known as emergent or beginning reading.This research aims to improve the beginning reading skills of children at PAUD Imanuel Maubele through the use of picture word card media. The research employs a Classroom Action Research (CAR) approach following the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages, implemented in two cycles. The study involved 24 children aged 5-6 years, consisting of 14 girls and 10 boys. Data were collected using observation sheets.The pre-action observations showed that the children's beginning reading skills were still low, with an average achievement of only 42.59%. After implementing the first cycle, the average increased to 68.34%, with two children reaching the class success indicators. In the second cycle, the results showed a significant improvement, with an average achievement of 95.57%. These findings indicate that using picture word card media can effectively enhance the beginning reading abilities of early childhood students at PAUD Imanuel Maubele.